Proyecto de factibilidad para la creación de un centro gerontológico en el cantón La Mana, año 2013 - Morán Intriago, Amelia Liceth (2015)
This research project aims to develop a feasibility study for the creation of a geriatric center in the canton's Mana, Cotopaxi Province during 2013. For this purpose the following objectives: Conduct a market study to determine the level of acceptance of the services of a geriatric center in the market for Mana. Estimate the amount of investment and operation costs, through a technical study. Determining financial ratios and establish the level of profitability of the project through an economic and financial study. Within the methodology used are the types of research, methods such as inductive and deductive techniques, research design and the population from which the sample of 380 citizens of Canton Mana was taken, which were surveyed allowed them to determine the feasibility of the project. Through the feasibility study we conclude the following: The market survey showed that the level of acceptance of the services of a geriatric center in the market Maná, reached 71%, this value corresponds to the purchase intent target market, in strata medium-medium and medium-low. The project is feasible because the amount of investment and operation costs relating to a geriatric center in the canton's Mana, through technical study yielded the following items and components: Fixed Investment of $ 217860; a gain of $ 46.005,11 Financial ratios were: Net Present Value reaches the amount of $ $ 48322,69, the internal rate of return is 21%, which is higher than the opportunity cost of money, demonstrating that the project is economically viable.